Duration vs Discipline: Uncovering Therapy Adherence Antiretrovirals in People with HIV - Asmara, Yusuf Vindra; -, Evi Nurhayatun; - Putri, Desy Puspa (Indonesian Journal of Medicine, 2025)
Background: HIV is a retrovirus targeting the immune system, requiring continuous antiretro-viral therapy (ARVs) for effective management. In Indonesia, 329,581 HIV cases were documented from 1987 to 2022, with only 51% receiving ARVs. Adherence is crucial for treatment success, but prolonged therapy may impact medication compliance. This study investigates the correlation between ARV treatment duration and adherence levels at Dr. Moewardi Hospital. Subjects and Method: A cross-sectional observational study was conducted at the Voluntary Counseling and Testing (VCT) clinic, involving 60 HIV-diagnosed individuals selected through purposive sampling. Therapy duration was extracted from medical records, and adherence was assessed using the MMAS-8 questionnaire during June and July 2024. Bivariate analysis employed the Spearman correlation coefficient test. Results: The study sample predominantly consisted of individuals aged 36-45 years, with the majority having completed high school education. The mean therapy duration was 5.60 ± 3.64 years, ranging from 1 to 15 years. Adherence levels varied significantly, with 48.3% of patients demonstrating high adherence, characterized by a mean therapy duration (Mean= 6.86 years; SD= 3.62). Moderate adherence was observed in 16.7% of participants, with a mean therapy duration (Mean= 6.60 years; SD= 2.55). Low adherence was found in 35.0% of patients, associated with a shorter mean therapy duration (Mean= 3.38 years; SD= 3.14). There was a positive and sig¬nificant association between therapy duration and adherence level (r= 0.415; p= 0.001). Conclusion: The length of antiretroviral therapy (ART) exhibits a favorable correlation with adherence levels among individuals living with HIV. An extended duration of the therapeutic regimen is correlated with an enhanced adherence rate. This observation underscores the significance of sustained support, particularly during the initial years of the treatment course.